SP0180 Advances in The Genetics of Chronic Pain Syndromes: How Twin Studies Help. (15th July 2016) - Williams, F.M.
Abstract : Chronic widespread musculoskeletal pain and fibromyalgia are increasingly viewed as spectrum disorders, and they co-exist with many other pain syndromes within individuals and their families. Large scale epidemiological studies are superior to clinical collections for providing evidence of overlap in the chronic pain syndromes and allowing the genetic and environmental risk factors to be determined. Twin registers are a special case of this and allow many different types of study, which provide answers to important questions in chronic pain. In this talk I will introduce the following concepts:- 1. The chronic pain syndromes 2. The concept of heritability 3. TwinsUK – an NIHR BioResource at KCL 4. Twin study designs which help shed light on chronic pain mechanisms Disclosure of Interest: None declared